Systematic functional analysis of rab GTPases reveals limits of neuronal robustness to environmental challenges in flies - Kohrs, Friederike; Daumann, Ilsa-Maria; Pavlović, Bojana; Jin, Eugene Jennifer; Kiral, F Ridvan; Lin, Shih-Ching; Port, Fillip; Wolfenberg, Heike; Mathejczyk, Thomas F; Linneweber, Gerit A; Chan, Chih-Chiang; Boutros, Michael; et al. (eLife, 2021)
Rab GTPases are molecular switches that regulate membrane trafficking in all cells. Neurons have particular demands on membrane trafficking and express numerous Rab GTPases of unknown function. Here, we report the generation and characterization of molecularly defined null mutants for all 26 rab genes in Drosophila. In flies, all rab genes are expressed in the nervous system where at least half exhibit particularly high levels compared to other tissues. Surprisingly, loss of any of these 13 nervous system-enriched Rabs yielded viable and fertile flies without obvious morphological defects. However, all 13 mutants differentially affected development when challenged with different temperatures, or neuronal function when challenged with continuous stimulation. We identified a synaptic maintenance defect following continuous stimulation for six mutants, including an autophagy-independent role of rab26. The complete mutant collection generated in this study provides a basis for further comprehensive studies of Rab GTPases during development and function in vivo.
Gesehen am 03.07.2021